ANALISIS PROSEDUR PENGHAPUSAN BARANG MILIK DAERAH BERUPA KENDARAAN OPERASIONAL BERDASARKAN PERATURAN MENTERI DALAM NEGERI (PERMENDAGRI) NOMOR 7 TAHUN 2024 PADA KANTOR BADAN KEUANGAN DAN ASET DAERAH (BKAD) KABUPATEN SUMENEP - Diah Ajeng Kusuma Wardani Hamzah,; Rachmat Hidayat,; Sri Rahayu, (Juremi: Jurnal Riset Ekonomi, 2025)
The management of regional-owned assets must be conducted in a transparent, effective, and accountable manner to provide optimal benefits for governmental operations and public services. One critical aspect of asset management is the disposal procedures, particularly concerning operational vehicles that are no longer functional or productive. This study aims to analyze the implementation of asset disposal procedures for operational vehicles at the Regional Finance and Asset Office (Badan Keuangan dan Aset Daerah – BKAD) of Sumenep Regency, in accordance with the provisions outlined in the Minister of Home Affairs Regulation No. 7 of 2024 on the Management of Regional-Owned Assets. Data collection of this study was carried out using qualitative methods, including in- depth interviews, direct observation, and document analysis. The data were analyzed through Miles and Huberman’s qualitative data analysis framework, which consists of data reduction, data display, verification, and conclusion drawing. The primary data sources were officials from the Asset Division and the Asset Disposal Sub-Division within BKAD of Sumenep Regency. Findings indicate that BKAD Sumenep has implemented asset disposal procedures in compliance with previously established regulations. However, the implementation of the newly issued Minister of Home Affairs Regulation No. 7 of 2024 remains ongoing. Despite progress, several challenges persist, including delays in inter-agency coordination and inadequate updating of the asset information system. To enhance the effectiveness and accountability of the asset disposal procedures, it is recommended to improve human resource competencies and increase the integration of asset information systems